2000
DOI: 10.1007/s100050010047
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spectroscopic Imaging of Magnetotactic Bacteria: Magnetosome Morphology and Diversity

Abstract: Magnetotactic bacteria from aquatic environments were analyzed with the electron spectroscopic imaging technique. Rod-shaped bacteria and cocci were present in most of the samples observed. Magnetotactic multicellular aggregates were also observed at some of the sampling sites. The use of electron spectroscopic imaging allowed the observation of magnetosomes inside magnetotactic microorganisms with exceptional clarity. The number, size, and morphology of magnetosomes, as well as their ultrastructural spatial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…3E of Flies et al ., 2005; fig. 1D of Amann et al ., 2006); and freshwater lagoons (Jacarepiá Lagoon, Saquarema, Brazil) (data not shown) and brackish waters (Lagoa de Cima, Rio de Janeiro) in south‐eastern Brazil (figs 2.2 and 2.4 of Lins et al ., 2000).…”
Section: Discussionmentioning
confidence: 92%
“…3E of Flies et al ., 2005; fig. 1D of Amann et al ., 2006); and freshwater lagoons (Jacarepiá Lagoon, Saquarema, Brazil) (data not shown) and brackish waters (Lagoa de Cima, Rio de Janeiro) in south‐eastern Brazil (figs 2.2 and 2.4 of Lins et al ., 2000).…”
Section: Discussionmentioning
confidence: 92%
“…However, in none of these examples it was revealed whether the detected phylotypes were forming magnetosomes. In addition, recent findings indicated that the geographical distribution of magnetosome‐forming ‘ Candidatus M. bavaricum’‐like bacteria is not restricted to calcareous sediments of Lake Chiemsee, but closely related magnetic organisms were also reported from sediments in Bremen, Germany (Flies et al ., 2005a), Beijing, China (Lin and Pan, 2009; Lin et al ., 2009), the Seine River near Paris, France (Isambert et al ., 2007) and Brazil (Lins et al ., 2000). However, since the seminal description of ‘ Candidatus M. bavaricum’ (Spring et al ., 1993), no progress was made concerning its further ecological, physiological and genetic characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Although the number of sequenced genomes from the deep‐branching MTB remains low with some of them remaining partially sequenced, this study paves the way of the evolutionary history of magnetotaxis in the early‐diverging MTB. With the ever increasing number of study that seek at exploring the biodiversity, the deep‐branching MTB with their unique morphologies have been observed all over the world [(Lins et al ., ; Lefèvre et al ., 2010; 2011; Lin et al ., 2011; 2012); Fig. ].…”
mentioning
confidence: 99%